"These forecasts may be substantially different from actual results." The use of epistemic modal markers in English and German original letters to shareholders and in English-German transla - Kranich, Svenja; Bicsár, Andrea (Linguistik Online, 2012)
Letters to shareholders (i. e. the first part of a company’s Annual Report) represent an interesting genre for the analysis of epistemic modal expressions. They serve the function to present a short overview of the company’s main achievements as well as an outlook into the future. They additionally serve a more marketing-oriented goal: to inspire confidence in the company. Epistemic modal expressions (e. g. may, perhaps, probably) are used in texts for two main reasons: Firstly, speakers can signal with these markers that they have content-based reasons to be unsure about the states of affairs they are talking about. This type of use can be expected to be typical in the context of predictions of future developments. Secondly, speakers can use them for interpersonal reasons, to open up the discursive space for alternative positions, leaving the readers their right to form their own opinion. This type of use can be expected in positive evaluations of one’s own company, which are thus presented in a mitigated way, avoiding the impression of boasting. It is in particular the second type of use that can be expected to be highly sensitive to cultural differences. The present paper analyzes to what extent US-English and German letters to shareholders differ in the use of these markers, and how these differences are reflected in English-German translations. Our quantitative analysis of the distribution of all epistemic modal markers in a multilingual corpus comes to the conclusion that there are notable differences between English and German original texts. Unlike in other studies on English-German translations (e. g. Kranich/House/Becher 2012), however, we arrive at the conclusion that the English-German translations are very closely adapted to the target-language conventions and show little interference from the English originals.